PENGARUH PENDIDIKAN DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI KABUPATEN ROKAN HULU PROVINSI RIAU - Nobel Aqualdo, Aggy Marsya Putra Lapeti Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of education variables and population in Rokan Hulu Regency, Riau Province. The method of analysis in this study uses secondary data which is classified as time series data which is descriptive and quantitative. The data analysis technique in this study uses multiple linear regression model estimation with statistical tests (t test, F test, coefficient of determination R2, correlation coefficient), and classical assumption test. The results of the study using a partial regression coefficient test (t test) showed that the independent variable education with a probability of (0.0005 <0.05) means that it has a positive and significant effect on poverty in Rokan Hulu Regency, Riau Province. While the population variable has a positive and insignificant effect on poverty in Rokan Hulu Regency, Riau Province. The F test shows that together the three variables of education and population have a significant effect on poverty in Rokan Hulu Regency, Riau Province with prob (F-statistics) of 0.000304 <0.05 and R2 of 87.28%. Keywords :   Education,   Population,  Poverty.